POLA KOMUNIKASI PENYANDANG TUNARUNGU SEKOLAH LUAR BIASA (SLB) NEGERI PEMBINA PEKANBARU - Yenisma Safitri; Mangatur Sinaga; Auzar Auzar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThis study aimed to describe the communication patterns and sentence structure of deaf students at Special School (SLB) Negeri Pembina Pekanbaru. The data was in the form of conversation whether uttered or gestured by the 19 participants. The method of this study was descriptive. The data was collected by using observation, video recording, notes, and literature study. To analyze the data, the writer recorded the conversations done by the deaf students, noted the important information about the respondents from the conversation, collected the video of their conversation, translated various models of their communication, classified and identified the patterns of their communication, and noted the patterns found. The theories used in this study were Cangara (2010), Nurudin (2007), Effendy (2009), Tarigan (1990), Muhammad (2002), Hakim (2007), Rakhmat (2007), Dwidjosumarto (2006), Hernawati (2007), Ahmad (1997), Kridalaksana (1986), and Mulyana (2005). The results of this study found two patterns of communication done by the deaf students including diadik and small group communication. Based on the category of sentence structure, the students used nominal as dominated sentence. The specific characteristics of the sentence used by the deaf students at Special School (SLB)Pembina were brief and repeated frequently.Keywords : Communication Patterns, Sentence Structure, Deaf.